PROBLEMS OF CONTINUED AIRWORTHINESS THE AIRCRAFT FLEET OF UKRAINE - Puchikov, Yuriy; Molodtsov, Nikolay; Rugain, Alexander; Popov, Dmitriy (Proceedings of National Aviation University (archive), 2014)
The state and the problems associated with continuing airworthiness of the existing fleet of Ukrainianaircraft of Soviet and foreign production, through the creation of centers for its maintenance with the involvement ofyoung professionals